2007
DOI: 10.1172/jci32533
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 triggers malignant features in mammospheres from human ductal breast carcinoma and normal mammary gland

Abstract: High serum levels of IL-6 correlate with poor outcome in breast cancer patients. However, no data are available on the relationship between IL-6 and mammary stem/progenitor cells, which may fuel the genesis of breast cancer in vivo. Herein, we address this issue in the MCF-7 breast cancer cell line and in primary human mammospheres (MS), multicellular structures enriched in stem/progenitor cells of the mammary gland. MS from node invasive breast carcinoma tissues expressed IL-6 mRNA at higher levels than did M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
614
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 703 publications
(659 citation statements)
references
References 50 publications
38
614
1
6
Order By: Relevance
“…IL‐8 is also associated with cancer stem cell‐like properties, and its expression correlates with poor prognosis in human pancreatic cancer (Chen et al ., 2014). Of these inflammatory cytokines, IL‐6 is reported to play especially important roles in the development of lung and breast cancers (Gao et al ., 2007; Sansone et al ., 2007). With regard to the effect of these cytokines on the EMT, previous reports focused mainly on the regulation of EMT‐related downstream factors, with ZEB1 reported as a target gene of certain inflammatory cytokines (Liu et al ., 2015; Peinado et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐8 is also associated with cancer stem cell‐like properties, and its expression correlates with poor prognosis in human pancreatic cancer (Chen et al ., 2014). Of these inflammatory cytokines, IL‐6 is reported to play especially important roles in the development of lung and breast cancers (Gao et al ., 2007; Sansone et al ., 2007). With regard to the effect of these cytokines on the EMT, previous reports focused mainly on the regulation of EMT‐related downstream factors, with ZEB1 reported as a target gene of certain inflammatory cytokines (Liu et al ., 2015; Peinado et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The ZEB1‐regulated inflammatory phenotype identified in this study was characterized by enhanced breast cancer cell growth, fibroblast proliferation, and PMN‐MDSC accumulation, although each of these was observed only in certain cell types and was context dependent. The correlation between IL‐6 production and cancer proliferation has been reported in various types of cancers, including lung, prostate, and breast cancers (Gao et al ., 2007; Giri et al ., 2001; Sansone et al ., 2007; Yamaji et al ., 2004). IL‐6 secreted by cancer cells activates STAT3, and induces downstream events, including cancer cell proliferation and apoptosis inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Second, as two important transcriptional factors, NF-κB and STAT3 cooperatively bind at a subset of gene promoters to collaboratively induce their target genes expression (Yang et al, 2007). Third, many cytokines like IL-6 induced by NF-κB or STAT3 can feedback to induce STAT3 and NF-κB activation (Gao et al, 2007;Sansone et al, 2007;Grivennikov and Karin, 2008). Through their functional interaction, NF-κB and STAT3 collaboratively promote tumor development via induction of pro-tumorigenic genes including genes in angiogenesis and hypoxia, chemokines and immunosuppressive cytokines (Bollrath and Greten, 2009;Atkinson et al, 2010;He and Karin, 2011).…”
Section: Stats Signaling Transduction Pathwaymentioning
confidence: 99%
“…To assess the effects of LLNle and DAPT on the NOTCH pathway in GBM TICs, we examined the expression of NICD transcriptional target genes JAG1, HES1, HEY1, and HEY2 (32)(33)(34) as evaluated by the GeneChip microarray studies. The values of mRNA expression for these genes showed that the effects of the two drugs were not homogeneous across the three patients (see Supplementary Data S5).…”
Section: Llnle and Dapt Effects On Notch Target Genesmentioning
confidence: 99%